To Beam or Not to Beam: A Study of Remote Telepresence Attendance at an Academic Conference - Neustaedter, Carman; Venolia, Gina; Procyk, Jason; Hawkins, Daniel (Proceedings of the 19th ACM Conference on Computer-Supported Cooperative Work & Social Computing, 2016)
Attending and presenting at conferences is a core part of academic and industrial research. Yet it can sometimes be challenging to attend conferences due to travel restrictions, time limitations, or accessibility challenges. To understand how people may be able to attend conferences remotely, we explored the use of commercial telepresence robots called Beams at Ubicomp/ISWC 2014. Seven people attended the conference remotely and used Beams to attend presentations, ask questions, and participate in break mingling activities. We collected data of their activities and conducted an online survey with the broader set of conference attendees. Results show that telepresence robots supported attendance at a basic level and even empowered those with accessibility challenges. However, issues related to identity, interaction, navigation, and privacy emerged. We present recommendations for future telepresence attendance at conferences focused on balancing these concerns with the benefits participants received.